2018
DOI: 10.1177/1074248418788575
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Cardioprotection: A Natural Defense Against Lethal Myocardial Ischemia–Reperfusion Injury and Potential Guide to Cardiovascular Prophylaxis

Abstract: Similar to ischemic preconditioning, high-intensity exercise has been shown to decrease infarct size following myocardial infarction. In this article, we review the literature on beneficial effects of exercise, exercise requirements for cardioprotection, common methods utilized in laboratories to study this phenomenon, and discuss possible mechanisms for exercise-mediated cardioprotection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 161 publications
(186 reference statements)
0
18
0
3
Order By: Relevance
“…Several studies have indicated that regular practice of physical exercise constitutes a physiological condition that can potentially stimulate the cardioprotective response [51,52,53]. It is well established that moderate exercise is an effective and economic way to prevent and treat cardiovascular diseases, because exercise induces cardiac hypertrophy and neo-angiogenesis, essential determinants for cardioprotection [51,52,53]. Similar to ischemic preconditioning, the practice of moderate (1 to 3 episodes of exercises per week) and high-intensity exercise can decrease infarct size following myocardial infarction [51,52,53].…”
Section: Cardioprotective Strategies Against Myocardial Lesions Camentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that regular practice of physical exercise constitutes a physiological condition that can potentially stimulate the cardioprotective response [51,52,53]. It is well established that moderate exercise is an effective and economic way to prevent and treat cardiovascular diseases, because exercise induces cardiac hypertrophy and neo-angiogenesis, essential determinants for cardioprotection [51,52,53]. Similar to ischemic preconditioning, the practice of moderate (1 to 3 episodes of exercises per week) and high-intensity exercise can decrease infarct size following myocardial infarction [51,52,53].…”
Section: Cardioprotective Strategies Against Myocardial Lesions Camentioning
confidence: 99%
“…It is well established that moderate exercise is an effective and economic way to prevent and treat cardiovascular diseases, because exercise induces cardiac hypertrophy and neo-angiogenesis, essential determinants for cardioprotection [51,52,53]. Similar to ischemic preconditioning, the practice of moderate (1 to 3 episodes of exercises per week) and high-intensity exercise can decrease infarct size following myocardial infarction [51,52,53]. It has been proposed that moderate exercise induces the intracellular IGF-1-PI3K-Akt, NO, C/EBPβ, and PGC-1α signaling pathways, promoting protection against cardiac ischemic disease, cardiac aging and cardiac metabolic derangement [54].…”
Section: Cardioprotective Strategies Against Myocardial Lesions Camentioning
confidence: 99%
“…Regarding the intensity of exercise, this may influence cardiovascular responses [22]. However, an optimal intensity for cardioprotection is not yet known [5]. In healthy individuals, cardiovascular changes seem to be more significant when subjected to the most intense effort [23].…”
Section: Effects Of Exercise Training In the Arterial Hypertensionmentioning
confidence: 99%
“…In healthy individuals, cardiovascular changes seem to be more significant when subjected to the most intense effort [23]. Although high intensities have shown important outcomes for cardiovascular health, such as improved endothelial function, individuals with CVD need greater care in the assessment and prescription of intense exercise [5].…”
Section: Effects Of Exercise Training In the Arterial Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation